DOWN PAYMENT (DP) DALAM PEMBIAYAAN MURABAHAH (Perspektif Fikih Muamalah) - Naimah Naimah (Syariah: Jurnal Hukum dan Pemikiran, 2013)
According to the Classical Islamic Literatures, down payment is clearly known as Urban in Arabic, or in Bahasa accepted by Panjar, which means an initial agreed contract into a transaction. Islamic Scholars arguably have different opinions in implementing down payment as a method in the transaction. There are some scholars who do not agree to put down payment as a particular way in the transaction, but others do. However, by exercising the quality of specific reasoning that is applied, and also the fact of the acceptance of the system of transaction, therefore this method of payment is generally accepted.